Implementasi program wajib infak dalam menumbuhkan kecerdasan interpersonal dan intrapersonal santri - Fauziah, Fina; Idawati, Khoirotul; Hanifudin; Kibtiyah, Asriana (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to analyze the implementation of the mandatory infak program in fostering the interpersonal and intrapersonal intelligence of students at the Walisongo Cukir Jombang Girls’ Islamic Boarding School. This study is motivated by the importance of character education based on Islamic values, which emphasizes not only cognitive aspects but also social and emotional aspects. The mandatory infak program is viewed as a character-building strategy through the cultivation of social acts of worship that embody the values of empathy, sincerity, responsibility, and self-control. This study employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The research subjects included boarding school caregivers, infak program administrators, and students. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the mandatory infak program is carried out systematically through mechanisms for collecting, recording, and distributing funds. This program has proven capable of fostering interpersonal intelligence in the form of empathy, social concern, and the ability to cooperate, as well as intrapersonal intelligence in the form of self-awareness, self-control, and personal responsibility. Supporting factors include the policies of the boarding school staff and adequate facilities, while inhibiting factors consist of technical and geographical constraints. Thus, the mandatory infak program serves as an effective medium in education. Abstrak Penelitian ini bertujuan untuk menganalisis implementasi program wajib infak dalam menumbuhkan kecerdasan interpersonal dan intrapersonal santri di Pondok Pesantren Putri Walisongo Cukir Jombang. Penelitian ini dilatarbelakangi oleh pentingnya pendidikan karakter berbasis nilai Islam yang tidak hanya menekankan aspek kognitif, tetapi juga aspek sosial dan emosional. Program wajib infak dipandang sebagai salah satu strategi pembinaan karakter melalui pembiasaan ibadah sosial yang mengandung nilai empati, keikhlasan, tanggung jawab, dan pengendalian diri. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Subjek penelitian meliputi pengasuh pondok, pengurus program infak, serta santri. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi program wajib infak dilakukan secara sistematis melalui mekanisme pengumpulan, pencatatan, dan penyaluran dana. Program ini terbukti mampu menumbuhkan kecerdasan interpersonal berupa empati, kepedulian sosial, dan kemampuan bekerja sama, serta kecerdasan intrapersonal berupa kesadaran diri, kontrol diri, dan tanggung jawab pribadi. Faktor pendukung meliputi kebijakan pengasuh dan fasilitas yang memadai, sedangkan faktor penghambat berupa kendala teknis dan geografis. Dengan demikian, program wajib infak menjadi media efektif dalam pendidikan karakter berbasis nilai Islam yang mengintegrasikan aspek religius, sosial, dan emosional dalam kehidupan santri.